Peer Education : Kesehatan Mental Remaja Untuk Pencegahan Gangguan Mental Remaja di Desa Ngadas - Indari, Indari; Yuni Asri; Aminah, Tien; Rizzal, Alfunnafi’ Fahrul (PPPM Stikes Banyuwangi, 2023)
The transition between childhood and maturity makes adolescence a challenging period. Physical and psychological alterations in adolescents will have an effect on their mental health. Continuing efforts are made to prevent mental disorders in adolescents, including here by educating adolescents about mental health. Teenagers in the village of Ngadas have never received any mental health education. This community service activity seeks to increase adolescents' knowledge of mental health, including efforts to prevent mental disorders in adolescents, through the dissemination of information. On January 5, 2023, 35 young people participated in this community service in the Ngadas Malang tourism village at SMPN 3 Poncokusumo Ngadas. Through the use of thought-stopping and five-finger hypnosis, this community service intervention provides mental health education and prevention efforts. The results of this community service activity demonstrate an increase in adolescents' mental health knowledge from 60% to 80% in the excellent category and participants were able to do stress management with thought-stopping and five-finger hypnosis, namely 85%. Education on adolescent mental health can increase adolescents' knowledge of adolescent mental health and stress management techniques they can implement.